Hepatoprotective Activity of Methanolic Extract of Leaves Parts of Chenopodium Album Linn on Carbon Tetrachloride Induced Hepatotoxicity in Waster Rats. - Jain, Himanshu; Sharma, Yogesh Kumar (Journal of Biomedical and Pharmaceutical Research, 2022)
The liver is among the most complex and important organ in the human body. Its primary function is to control the flow and safety of substances absorbed from the digestive system before distribution of these substances to the systemic circulatory system. Carbon tetra chloride is well- known hepatotoxin which is widely used to induce hepatotoxicity in laboratory animals. Chenopodium album Linn also known as frost Bilte, Pigweed (Canada), found to have antipruritic and antinociceptic, sperm immoblizing agent, cryptomeridiol and 8- alpha-acetoxycryryptomeridiol as growth promoting activity, (patak and pandey) Chenopodium album has reported hepatoprotective activity, antifungal, antihelminitic, contraceptive,  antipyretic and antinoceipetive activity. The present study was aimed to investigate hepatoprotective activity of alcoholic extract of leaves parts of Chenopodium album Linn on carbon tetrachloride induced hepatotoxicity in waster rats. The leaves of plant was dried under shed and then powdered. The Powder was packed into a Soxhlet apparatus, extract was concentrated in steam bath till the complete evaporation of the solvent. Administration of Carbon tetra chloride subcutanously (SC) in the lower abdomen, in a suspension of liq. paraffin (LP, 1:1 v\v) at the dose of 1ml\kg B.W. on alternate days of week showed significant increase in SGOT and SGPT. Methanol extract of Chenopodium album Linn. at dose of 200mg\kg B.W. P.O. (Group III) in a carbon tetra chloride treated groups cause significant decrease in SGOT and SGPT. Result of biochemical parameters of Chenopodium album Linn. (400 mg\kg B.W. P. O.), showed significantly arrestedin in rise of level of SGOT, SGPT was found in group IV. The standard drug Liv2R showed significant reduction in all parameters when compared to CCl4 treated groups. This study concluded that methanolic extract of Chenopodium album Linn. has hepatotprotective  effect in CCl4 induced liver damage. This effect is evident especially with high dose of Chenopodium album Linn. (400 mg\kg B.W. p.o) because it caused drastic fall in serum markers as compared to other doses of Doses of Chenopodium Album Linn.Abbreviations- serum glutamate oxaloacetatae transaminase (SGOT) and serum Glutamate Pyruvate Transaminase (SGPT)Keywords- Chenopodium album Linn., methanolic extract, carbon tetrachloride (CCl4), hepatotoxicity